Dampak Konflik Iran-Israel terhadap Necara Perdagangan Indonesia - Robbiatul Amalia; Abdul Madjid Musannah; Dies Nurhayati (Universitas Veteran Bangun Nusantara, 2026)
The ongoing Iran–Israel conflict has increased global geopolitical uncertainty and may affect the stability of international trade. Such conditions can influence the economies of many countries, including Indonesia, which is closely connected to global markets through export and import activities. This study aims to analyze the impact of the Iran–Israel conflict on Indonesia’s trade balance and identify its implications for national trade stability. The research employs a descriptive qualitative approach using a literature review method. Data were collected from secondary sources, including scientific journals, reports from international institutions, publications of Bank Indonesia, Statistics Indonesia, the World Bank, the International Monetary Fund, the World Trade Organization, and the United Nations Conference on Trade and Development published between 2020 and 2026. The findings indicate that the Iran–Israel conflict may affect Indonesia’s trade balance through rising global energy prices, disruptions in international supply chains, increasing logistics costs, and uncertainty in global market demand. Nevertheless, Indonesia’s export structure, which is dominated by primary commodities and selected manufactured products, provides opportunities to maintain trade performance amid global uncertainty. Furthermore, export market diversification and the strengthening of national product competitiveness are essential factors in sustaining trade stability. The study concludes that geopolitical conflicts in the Middle East have an indirect impact on Indonesia’s trade balance, highlighting the need for adaptive trade strategies to enhance the resilience of the national external sector.